answersLogoWhite

0


Best Answer

7n - 2 + 3n + 4 = 7n + 3n - 2 + 4 = 10n + 2 which can be simplified to 2(5n +1)

User Avatar

Wiki User

โˆ™ 2010-05-11 16:09:06
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

2 cards

What is the name of Steve on minecraft's name

What is love

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: 7n - 2 plus 3n plus 4 equals?
Write your answer...
Submit
Related questions

What is the perimeter of 7n plus 2 plus 6 plus 5n plus 7n plus 3n equals?

22n + 2.


What is 7n-2 plus 3n plus 4 equals?

10n+2


What is 7n - 2 plus 3n plus 4 simplfied?

Gather like terms. The - 2 and 4; the 7n and 3n. 7n - 2 + 3n + 4 = 10n + 2


What is the sum of the equation 3n plus 4n equals -14?

3n + 4n = -14 7n /7 = -14 /7 n = -2


What is 7n plus 2 plus 3n-8?

All you do is look for like terms such as 7n and 3n; 2 and 8 Then you do 7n+3n=10 n And ........... 2-8=-6 The answer is 10n-6 if you still dont get it contact me(:


What is n if 10n plus 3 equals 7n plus 5?

10n + 3 = 7n + 53n = 2n = 2/3


.5m plus 7n equals 6.4 2m - 7n equals 6?

(10, 2)


3n-2 divide by 8 equals n plus 4 divide by 5 what is n?

(3n-2)/8 = (n+4)/55(3n - 2) = (n+4)815n - 10 = 8n + 327n = 42n = 6


What is the answer to 5m plus 7n equals 6.4 2-7n equals 6?

2 - 7n = 6therefore 7n = 2 - 6 = -4 and so n = -4/7 Then 5m + 7n = 6.4 becomes 5m - 4 = 6.4 so that 5m = 10.4 and then m = 10.4/5 = 2.08


What is 3N plus 2 plus 3N plus 2?

3n+2+3n+2=6n+4


Solve 7n plus 2 equals 4n plus 17?

7n + 2 = 4n + 17Subtract 2 from each side:7n = 4n + 15Subtract 4n from each side:3n = 15Divide each side by 3:n = 5


How do you get this 3n plus 2 plus (3n plus 3 - 3n plus 1)?

3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6


If n is 2 3n plus 1 equals 7?

3n+1=7 3*2+1=7


What is the answer to 5n-7 equals 3n plus 2?

4n


What is 9n-2 equals 7n plus 50?

9n-2=7n+50 7n+9n=50+2 16n=52 n= 3.25


What is the answer to 3 plus 3n equals 9 plus 2n plus 4n?

3 + 3n = 9 + 2n + 4n n = -2


How do you find the answer to m plus 3n equals 7 n equals -2 0 1?

m + 3n = 7n = -2017n = -201n = -201 / 7n = -28.71m + 3n = -201m + 3(-28.31) = -201m - 86.14 = -201m = -201 + 86.14m = -115So the final answer will be, m = -115 and n = -28.71I hope this makes sense. :)


What is -2n plus 9n?

7n -1n,0n,1n,2n,3n,4n,5n,6n,7n 1 2 3 4 5 6 7 8 9


What is the perimeter of a rectangle with width 3n plus 2 and length n-1?

perimeter equals 2 times width plus 2 times length so, perimeter equals 2(3n+2)+2(n-1) = 6n+6+2n-2 = 8n+4.


2-4N equals 2 plus 3N?

2 - 4N = 2 + 3NSubtract 2 from each side:-4N = 3NAdd 4N to each side:0 = 7NN = 0That's the only value of ' N ' for which the given equationcan become a true statement.


How do you solve -7n-8 plus 6 equals 13-2?

-7n - 8 + 6 = 13 - 2 Add 2 to each side: -7n - 8 + 6 + 2 = 13 simplify: -7n = 13 n = -13/7 = -16/7


What is the sum of the first 50 terms of the sequence an equals 3n plus 2?

3925


How do you get 3 to the power of n plus 2 plus (3 to the power of n plus 3 minus 3 to the power of n plus 1)?

3n+2 + (3n+3 - 3n+1) = 3n+1+1 + (3n+1+2 - 3n+1) = 3*3n+1 + (9*3n+1 - 3n+1)= (3+9-1)*3n+1 = 11*3n+1.


What is 4n-8 equals 3n plus 2?

4n-8=3n+2 4n=3n+2+8 4n=3n+10 4n-3n+10 n=10 N = 10


What is 3n plus 6 equals 18?

3n+6=18 n+2=6 n=4